Enhancing Students’ Spiritual Awareness through Understanding Human Physiology in Biomedical Science Course - Nur Al Marwah Asrul; Taufiq Al Islam Asrul; M Burga (Al-Musannif, 2025)
The increasing amount of information among the younger generation is not directly correlated with the enhancement of their spiritual awareness. This is due to the fact that science education emphasizes cognition rather than emotion and fails to include Islamic principles into its curriculum. This study seeks to examine the enhancement of students’ spiritual consciousness following their comprehension of human physiology in the Basic Biomedical Sciences course. This qualitative study purposively chose informants from among instructors and students. Data were gathered by observation, interviews, and documentation methods. The gathered data were examined by descriptive analysis methods, and their validity was assessed utilizing triangulation procedures. The study's findings demonstrate that Islam (Qur’anic verses) pertains to the concept of human physiology. Comprehending the subject of human physiology in conjunction with Islamic studies helps enhance students’ spiritual consciousness. This study underscores the significance of assembling a curriculum development committee comprising specialists in education, Islamic studies, and human physiology to create an integrated curriculum. Instructors must also be capable of utilizing the subject of human physiology to demonstrate the Greatness and Omnipotence of Allah swt.